1992
DOI: 10.1039/jm9920201249
|View full text |Cite
|
Sign up to set email alerts
|

Phase relationships and electrical properties of Ti3O5, CrTi2O5and the pseudobrookite-type systems MgxTi3 –xO5and LixTi3 –xO5

Abstract: The structural phase transitions and electrical properties of Ti30,, the pseudobrookite series Li ,Ti ,-,O, and MgxTi3-,0,, and of v305 structure type CrTi,05 have been studied by high-temperature X-ray diffraction, differential scanning calorimetry, and d.c. conductivity measurements. Ti30, undergoes a complex transformation between 440 and 515 K from semiconducting a-Ti305 to metal-like P'-Ti305 with orthorhombic pseudobrookite structure. The intermediate formation of the monoclinic /?-Ti,O, polymorph involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The crystal structure of b-Ti 3 O 5 is constituted in terms of distorted TiO 6 octahedrons that are linked by sharing edges and corners to form an infinite three dimension framework. b-Ti 3 O 5 undergoes b-Ti 3 O 5 (C2/m)-a-Ti 3 O 5 (C2/m) phase transition at approximately 460 K, and then to orthorhombic structure (Cmcm) at about 500 K, demonstrated through diverse experimental methods, such as X-ray diffraction (XRD), differential scanning calorimetry (DSC), conductivity measurements, magnetic measurements and so on [11][12][13][14][15][16][17]. While on compression up to 38.6 GPa at room temperature, no phase transition was observed in XRD experiments [18].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of b-Ti 3 O 5 is constituted in terms of distorted TiO 6 octahedrons that are linked by sharing edges and corners to form an infinite three dimension framework. b-Ti 3 O 5 undergoes b-Ti 3 O 5 (C2/m)-a-Ti 3 O 5 (C2/m) phase transition at approximately 460 K, and then to orthorhombic structure (Cmcm) at about 500 K, demonstrated through diverse experimental methods, such as X-ray diffraction (XRD), differential scanning calorimetry (DSC), conductivity measurements, magnetic measurements and so on [11][12][13][14][15][16][17]. While on compression up to 38.6 GPa at room temperature, no phase transition was observed in XRD experiments [18].…”
Section: Introductionmentioning
confidence: 99%
“…An increase of the dopant metal content to 7−8% or higher 18 destabilizes the monoclinic polymorph completely and the structure converts to the orthorhombic α form at room temperature. This has been demonstrated with an extensive range of metal ions including Sc 3+ , Cr 3+ , Li + , Fe 3+ , Mg 2+ , Al 3+ and V 3+ . This phase transition to the orthorhombic polymorph on cation doping is caused by the destruction of the charge ordered state present in Ti 3 O 5 that creates the monoclinic β modification . It can be observed that it is the change in valance that has the principal effect on phase transition by comparing the doping of Mg 2+ and Li + into M x Ti 3- x O 5 .…”
mentioning
confidence: 96%
“…Ti(III/IV) oxide, α-Ti 3 O 5 , (oS32) crystallizes in an orthorhombic crystal structure with space group Cmcm (no. 63) (Figure 2b) [91]. Taking the magnetic ordering into account changes the space group to the subgroup Cm (8).…”
Section: Magnetic Binary 3d-metal Oxidesmentioning
confidence: 99%